منهج الشيخ عبد القادر الجيلاني في التربية الروحية - شكيمة, عيسى (University of eloued جامعة الوادي, 2018)
"هذا البحث ومن خلال عنوانه: منهج الشيخ عبد القادر الجيلاني في التربية الروحية تطرقت فيه للحديث عن جوانب مهمة من سيرة الشيخ العطرة في جانبها الشخصي والعلمي, التي حظيت بهالة من التقدير والاحترام, مقدما لها بالحديث عن عصره. كما تعرضت أيضا فيه للحديث عن منهج هذا العلم في التربية الروحية, والذي جمع فيه بين ما يُعرف عند الصوفيين بالشريعة والحقيقة, معتمدا في ذلك على ضرورة التمسك بالكتاب والسنة, متكلا على مجالس الوعظ والإرشاد في إنجاح منهجه الذي عرف نجاحا منقطع النظير." "This research and through the title: the approach of Sheikh Abdul Qadir Jilani in spiritual education addressed to talk about important aspects of the biography of Sheikh fragrant in its personal and scientific, which received a halo of appreciation and respect, in advance of her talk about his age. She was also exposed to the approach of this science in spiritual education, which brought together what is known as the Sufis by law and truth, relying on the need to adhere to the book and the Sunnah, relying on the boards of preaching and guidance in the success of his method, which was known as an unrivaled success."
Keywords: منهج الشيخ عبد القادر الجيلاني ،التربية الروحية ،مجالس الوعظ والإرشاد.; Shaykh 'Abd al-Qadir al-Jilani's approach to spiritual education, in which he combines the law and the truth, relying on the necessity of adhering to the Qur'aan and Sunnah, based on the preaching and guidance councils